2007
DOI: 10.1002/ptr.2149
|View full text |Cite
|
Sign up to set email alerts
|

Screening of active ingredients of herbal medicine for interaction with CYP450 3A4

Abstract: A two-step algorithm is adopted in the screening of herbal species which possess significant inhibitory effects on cytochrome P450 3A4 (CYP450 3A4). The algorithm comprises an initial stage of high throughput screening with Herbochip for the identification of herbal fractions that exhibit interactions with CYP450 3A4. Fifty commonly used TCM species were screened with seven showing a positive signal reflecting interaction. In the inhibition assays that followed, six of the seven species gave a signal. Sophora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The success of this technology may be attributed by direct interaction between herbal extracts and diseased-related target proteins, which increase higher possibility of those extracts to act as a regulator to diseases. Prior to the current study, we have examined cytochrome P450 3A5 [21] and TNF-α [22] and the results, respectively, led to the discovery of S. flavescens extract and G. wilfordii extract for possible application in anti-HIV and anti-inflammatory drug development [21, 22]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success of this technology may be attributed by direct interaction between herbal extracts and diseased-related target proteins, which increase higher possibility of those extracts to act as a regulator to diseases. Prior to the current study, we have examined cytochrome P450 3A5 [21] and TNF-α [22] and the results, respectively, led to the discovery of S. flavescens extract and G. wilfordii extract for possible application in anti-HIV and anti-inflammatory drug development [21, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…That is, chemical compounds from each herb are firstly fractionated and arrayed onto a surface-activated plastic chip, and hybridization is performed using a biotinylated protein target coupled with streptavidin-cy5 visualization system [20–22]. The platform has been successfully employed to screen herbal fractions that bind to protein targets such as cytochrome P450 3A4 (CYP450 3A4) and tumor necrosis factor-alpha (TNF-α) [21, 22]. These results lead to identification of CYP450 3A4 and TNF-α inhibitory activities in Sophora flavescens and Geranium wilfordii , respectively, which will then be used in the design of regimens for the treatment of HIV infection and rheumatoid arthritis [21, 22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it might be due to the inhibitory effect of SF on P450s. During the screening of herbal medicines that inhibit CYP3A activity, SF showed the highest potency, which suggested that there are CYP3A inhibitors in SF constituents (Lee et al, 2007). When CYP3A inducers and inhibitors are cotreated with drugs as CYP3A substrates, the effect of CYP3A inducers in drug-drug interactions is not significant, because the CYP3A inhibitors mask the effect of CYP3A inducers (Hafner et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the levels of inhibition obtained for each of the products additional tests could be suggested including in vivo interaction studies. The screening of the active ingredients of 49 herbal species for the potential inhibition of CYP3A4 was reported by Lee et al, (2007) using a CYP HerboChip ® . As these screening platforms become available it facilitates future research to determine the potential interactions between commonly used herbal medicines, natural foods and antiretroviral agents in order to prevent treatment failure and resistant HIV in HIV-infected individuals.…”
Section: Possible Therapeutic Failure or Development Of Drug Resistancementioning
confidence: 99%